Protected insect species in Italy: occurrence data from a 10-year citizen science initiative - Alice Lenzi; Silvia Gisondi; Marco Bardiani; Sönke Hardersen; Emanuela Maurizi; Fabio Mosconi; Gianluca Nardi; Alessandro Campanaro (Biodiversity Data Journal)
Occurrence data provide an important baseline for the planning of conservation strategies and for the protection of species and habitats. However, collecting such data usually requires energy and it is time-consuming. Recently, citizen science has been shown to be a suitable approach for the study and monitoring of biodiversity, as it allows for the collection of a large number of records, distributed spatially and over time. Additionally, this approach enable the generation of new knowledge and fosters environmental awareness in the participating volunteers.The present paper describes the data collected during the first citizenscience project on protected insect species in Italy. The dataset contains occurrence records of 31 taxa observed all over Italian national territory in 10 years for a total of 5,975 records. The aim of the project was to increase the knowledge, to document the distribution of the target taxa and to provide valuable data useful for the reporting of these insects as required by Articles 11 and 17 of the Habitats Directive.